2020
DOI: 10.1155/2020/3050487
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Metformin Complex Improves Polycystic Ovary Syndrome Comorbid Psychological Distress via Inhibiting NLRP3 Inflammasome Activation: A Prospective Clinical Study

Abstract: Objective. This study aimed at investigating the therapeutic effect and mechanism of pioglitazone metformin complex preparation (PM) in polycystic ovary syndrome (PCOS) comorbid psychological distress. Methods. Seventy-five patients with PCOS comorbid psychological distress were randomly allocated into the PM, metformin, and placebo groups. The primary efficacy measure was the change from baseline to week 12 on the Symptom Checklist 90-R (SCL-90-R) scores. NLRP3 inflammasome, IL-1β, IL-6, TNF-α, and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
2
14
1
1
Order By: Relevance
“…The superiority of metformin over empagliflozin in suppressing mTOR activity could be due to its role in inhibiting mTOR via AMPK-independent mechanisms such as Rag GTPases-dependent suppression of mTORC1 signaling ( Kalender et al, 2010 ). Concerning their effect on NLRP3 inflammasome, it was previously reported that metformin had a significant inhibitory effect on NLRP3 ( Bullón et al, 2016 ; Yang et al, 2019 ; Guo et al, 2020 ), which is opposite to our findings; in which metformin had an insignificant effect on the NLRP3 on the protein and the gene expression levels. In our study, individual administration of both drugs showed minimal inhibitory effect on NLRP3 inflammasome and the subsequent inhibition of caspase-1 activation, IL-1β, and IL18.…”
Section: Discussioncontrasting
confidence: 99%
“…The superiority of metformin over empagliflozin in suppressing mTOR activity could be due to its role in inhibiting mTOR via AMPK-independent mechanisms such as Rag GTPases-dependent suppression of mTORC1 signaling ( Kalender et al, 2010 ). Concerning their effect on NLRP3 inflammasome, it was previously reported that metformin had a significant inhibitory effect on NLRP3 ( Bullón et al, 2016 ; Yang et al, 2019 ; Guo et al, 2020 ), which is opposite to our findings; in which metformin had an insignificant effect on the NLRP3 on the protein and the gene expression levels. In our study, individual administration of both drugs showed minimal inhibitory effect on NLRP3 inflammasome and the subsequent inhibition of caspase-1 activation, IL-1β, and IL18.…”
Section: Discussioncontrasting
confidence: 99%
“…Certainly, our hypothesis of NLRP3 inflammasome involvement in inflammatory response in the ovary of obese mothers seems to be supported also by earlier reports showing NLRP3 inflammasome activation during development and treatment of PCOS (Guo et al 2020;F. Wang et al 2017).…”
Section: Discussionsupporting
confidence: 86%
“…1 The most common of these symptoms are depression and anxiety while others include bipolar disorder, schizophrenia spectrum disorder, eating disorder, personality disorder, sleeping disorder, and psychosis. 15,18,19 The exact pathophysiology of these conditions however is not yet fully understood. 20 Alexithymia, a personality trait characterized with difficulty to identify and distinguish emotions from bodily sensations, difficulty to describe and verbalize emotions, externally oriented thinking style, poverty of fantasy life or imaginative ability, and poor empathy is a risk factor for various physical and mental health problems including anxiety, depression, compulsive or addictive behaviours, physical symptoms, and potentially psychosomatic diseases.…”
Section: Mental Health Symptoms In Pcosmentioning
confidence: 99%